ANALISIS SEKTOR UNGGULAN DAN PENGEMBANGAN WILAYAH DI KABUPATEN BOLAANG MONGONDOW TIMUR - Elein ., Mamahit; Paulus A. Pangemanan; Charles R. Ngangi (Sam Ratulangi University, 2017)
This study aims to (1) identify the leading sectors in the economic structure of East Bolaang Mongondow Regency as information and consideration in (2) formulating regional development strategies. This study uses time series data from Gross Regional Domestic Product (PDRB) of East Bolaang Mongondow Regency and North Sulawesi Province in 2010 - 2016. The analysis tool used in this research is Klassen Tipology, Location Quotient (LQ), and Shift Share analysis to determine the leading sectors and SWOT analysis. The result of per sector analysis based on these three analytical tools shows that which is the leading sector in East Bolaang Mongondow Regency with criteria of advanced and fast growing sector, basic and competitive sector, there are 2 sectors: (a) agriculture, forestry and fishery sector, (b) mining and quarrying sectors. To formulate regional development strategy used SWOT analysis tool. Based on the SWOT analysis, the strategy of regional development at East Bolaang Mongondow Regency with the superior sector is in quadrant III so that the appropriate strategy is turn around strategy. The Weakness Opportunity Strategy in Quadrant III, means minimizing weaknesses by taking advantage of opportunities.